2022
DOI: 10.3389/fpsyg.2022.1017750
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation of business model innovation

Abstract: Because of the rising labor costs and the trade impact after joining the World Trade Organization, the textile industry in Taiwan has encountered many operational and production problems and obstacles. In addition, the lack of knowledge and resources for the digital transformation required to improve business performance has led to poor production and decision-making efficiency, and stagnant R&D for textile product innovation. In order to improve business operations, enhance customer satisfaction and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Our research focused on exploring the information about the effects of multiple DT dimensions on BMs by interpreting disclosure from the IR ‘content element’ pertaining to it. In the current operating environment, the extant literature emphasised the importance of integrating digital technologies within the BM in order to remain competitive (Madlenak & Madlenakova, 2015), and several BM elements are impacted by the application of digital technologies, such as the value proposition, profit, cost structure, and processes (Tsai & Su, 2022). The disclosure of these elements has to be highlighted regardless of the benefit associated with them, although, as stated by Abhayawansa and Abeysekera (2009), it is also known that at times, information is given if the marginal benefit outweighs the information asymmetry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research focused on exploring the information about the effects of multiple DT dimensions on BMs by interpreting disclosure from the IR ‘content element’ pertaining to it. In the current operating environment, the extant literature emphasised the importance of integrating digital technologies within the BM in order to remain competitive (Madlenak & Madlenakova, 2015), and several BM elements are impacted by the application of digital technologies, such as the value proposition, profit, cost structure, and processes (Tsai & Su, 2022). The disclosure of these elements has to be highlighted regardless of the benefit associated with them, although, as stated by Abhayawansa and Abeysekera (2009), it is also known that at times, information is given if the marginal benefit outweighs the information asymmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Our research focused on exploring the information about the effects of multiple DT dimensions on BMs by interpreting disclosure from the IR 'content element' pertaining to it. In the current operating environment, the extant literature emphasised the importance of integrating digital technologies within the BM in order to remain competitive (Madlenak & Madlenakova, 2015), and several BM elements are impacted by the application of digital technologies, such as the value proposition, profit, cost structure, and processes (Tsai & Su, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2011) suggested that digital transformation is an organisational transformation that integrates digital technologies and business processes in the digital economy [18]. Tsai et al (2022) argued that digital technologies, as part of transformation, are becoming a part of business strategy, organisational culture, and structure [19].…”
Section: Digital Transformationmentioning
confidence: 99%
“…most scholars consider organizational innovation climate as a theoretical framework at the organizational level, a psychological climate that indirectly affects innovation performance of firms, Organizational innovation climate has been found to be an effective predictor of employee creativity and organizational innovation ( Hsu and Chen, 2017 ). Scholars have shown that organizational innovation climate can positively moderate the impact of perceived benefits and perceived risks on digital transformation ( Tsai and Su, 2022 ). The higher the organizational innovation climate, the greater the positive impact of positive emotional climate on innovation performance, and conversely the weaker the positive impact of negative emotional climate on innovation performance ( Dou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%